Genetic Inhibition of Plppr5 Aggravates Hypoxic-Ischemie-Induced Cortical Damage and Excitotoxic Phenotype - Sun, Yuxiao; Jin, Mei-fang; Li, Lili; Liu, Yueying; Wang, Dandan; Ni, Hong (Frontiers in Neuroscience, 2022)
Hypoxia-ischemia (HI) is the most common acute brain threat in neonates and a leading cause of neurodevelopmental impairment. Exploring the new molecular mechanism of HI brain injury has important clinical translational significance for the next clinical intervention research. Lipid phosphatase-related proteins (PLPPRs) are regulators of mitochondrial membrane integrity and energy metabolism. We recently found that Plppr5 knockout exacerbated HI impairment in some aspects and partially attenuated the neuroprotective effects of melatonin, suggesting that Plppr5 may be a novel intervention target for HI. The present study aimed to determine the long-term effects of gene knockout of Plppr5 on HI brain injury, focusing on the neuronal excitability phenotype, and to determine the effect of Plppr5 gene silencing on neuronal zinc metabolism and mitochondrial function in vitro. 10-day-old wild type (WT) mice and Plppr5-deficient (Plppr5–/–) mice were subjected to hypoxia-ischemia. Lesion volumes and HI-induced neuroexcitotoxic phenotypes were quantified together with ZnT1 protein expression in hippocampus. In addition, HT22 (mouse hippocampal neuronal cells) cell model was established by oxygen–glucose deprivation/reoxygenation (OGD/R) treatment and was treated with medium containing LV-sh_Plppr5 or control virus. Mitochondrial oxidative stress indicator ROS, mitochondrial ZnT1 protein expression and zinc ion content were detected. Results Plppr5-deficient mice subjected to hypoxia-ischemia at postnatal day 10 present significantly higher cerebral infarction. Plppr5-deficient mice were endowed with a more pronounced superexcitability phenotype at 4 weeks after HI, manifested as a reduced seizure threshold. ZnT1 protein was also found reduced in Plppr5-deficient mice as well as in mice subjected to HI excitotoxicity. Plppr5 knockout in vivo exacerbates HI brain injury phenotypes, including infarct volume and seizure threshold. In addition, knockout of the Plppr5 gene reduced the MFS score to some extent. In vitro Plppr5 silencing directly interferes with neuronal zinc metabolism homeostasis and exacerbates hypoxia-induced mitochondrial oxidative stress damage. Taken together, our findings demonstrate for the first time that Plppr5-deficient mouse pups exposed to neuronal hypoxia and ischemia exhibit aggravated acute brain injury and long-term brain excitability compared with the same treated WT pups, which may be related to the disruption of zinc and mitochondria-dependent metabolic pathways in the hippocampus. These data support further investigation into novel approaches targeting Plppr5-mediated zinc and mitochondrial homeostasis in neonatal HIE.